IMPLEMENTASI NILAI NILAI PANCASILA DALAM TRADISI MAULID NABI PADA MASYARAKAT KARANG PULE SEKARBELA - Muhamad Zaki; M Adli Rafif; Khairul Imam; Janeva Haerani; Latifatul Husna; Nila Widya Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pancasila, as the foundation of the Indonesian state, consists of five principles that serve as fundamental guidelines for national and civic life. The values of Pancasila not only reflect moral foundations but are also implemented in various aspects of society. One example is the tradition of celebrating the Maulid of Prophet Muhammad SAW in Karang Pule, Sekarbela. This study aims to explore the implementation of Pancasila values in the Maulid tradition within the local community, using a qualitative approach through interviews, observations, and documentation. The findings indicate that this tradition reflects each of the Pancasila principles: (1) Belief in One God, through the recitation of Barzanji and bequris activities that strengthen spirituality; (2) Just and Civilized Humanity, through food sharing and fostering social relationships; (3) Unity of Indonesia, through competitions that involve the entire community, strengthening togetherness amidst diversity; (4) Democracy Guided by the Wisdom of Deliberation/Representation, reflected in the discussions for fundraising and task division; and (5) Social Justice for All Indonesian People, realized through providing assistance to the poor and orphans. The Maulid tradition in Karang Pule not only strengthens religious identity but also fosters harmony between religious and national values. This research highlights the importance of local traditions in building community solidarity and implementing Pancasila values in daily life.